ROLE OF PREOPERATIVE ENDOVASCULAR EMBOLIZATION PRIOR TO MICROSURGICAL RESECTION IN ADULT UNRUPTURED SPETZLER–MARTIN GRADE II–III INTRACRANIAL ARTERIOVENOUS MALFORMATIONS: A NARRATIVE REVIEW - Agung Bagus Sista Satyarsa; Made Gemma Daniswara Maliawan; I Wayan Niryana; I Putu Ananta Wijaya Sabudi (CV. Adiba Aisha Amira, 2026)
Unruptured Spetzler–Martin (SM) grade II–III brain arteriovenous malformations (bAVMs) sit at the inflection point of management decisions: they are common enough to be encountered in everyday neurosurgical practice, yet diverse enough that the optimal treatment combination remains contested. Microsurgical resection is the only modality reliably producing immediate and complete obliteration, but adjunctive preoperative endovascular embolization (PE) has become routine in many centers, even though high-level evidence of clinical benefit is lacking. Objective: To synthesize contemporary literature on the indications, techniques, efficacy, and complications of PE prior to microsurgical resection in adult unruptured SM grade II–III bAVMs, with particular attention to the heterogeneity within the SM grade III category and to embolic-agent–related considerations. Findings: PE reliably reduces nidal blood flow and intraoperative blood loss but has not been shown in pooled analyses to improve obliteration rates or functional outcomes in unselected low- to intermediate-grade lesions. In SM grade II AVMs, surgery alone produces excellent results in most series and PE is generally unnecessary except for targeted vascular features. In SM grade III AVMs—a heterogeneous category better stratified by Lawton’s modification and by the Lawton–Young supplementary score—PE appears most useful for large lesions, deep perforator supply, and surgically inaccessible feeders. Onyx and other ethylene-vinyl alcohol copolymers have largely supplanted N-butyl cyanoacrylate (NBCA) for preoperative use in many centers, although evidence of clinical superiority is mixed. Embolization-related morbidity (transient or permanent neurological deficit in roughly 6–11%, hemorrhagic complication 2–6%) must be weighed against an annual rupture risk in unruptured AVMs that recent MARS data place around 1.4% per year. Conclusion: PE before microsurgery in unruptured SM grade II–III AVMs should be individualized rather than routine. It is most defensible for SM grade III lesions with high-flow, deep, or inaccessible feeders and least defensible for compact SM grade II lesions with superficial feeders. Decisions must be made in experienced multidisciplinary centers, recognizing that the cumulative morbidity of multi-modality treatment can equal or exceed that of well-selected surgery alone.